Influence of static magnetic field intensity on the separation and migration of Fe-rich bulks in an immiscible (Fe–C)–Cu alloy. Issue 18 (17th September 2019) - Li, Mingjun; Tamura, Takuya
ABSTRACT: In this study, we solidified an immiscible pseudo-binary (Fe–C)–50mass%Cu alloy in a static magnetic field and observed macro morphologies as a function of the magnetic flux density. The experimental result shows that the Fe-rich phase exhibits a single bulk when the alloy is solidified at a low magnetic flux density, while it is separated in to two smaller bulks at high magnetic flux densities and the distance between the bulks becomes larger with the increase of the magnetic flux density. The possible reason for the separation of the Fe-rich phase was simply proposed. As far as the migration of separated Fe-rich phase bulks is concerned, the thermoelectric effect between the Fe-rich and Cu-rich metals was considered, from which the thermoelectric body force could be exerted upon the Fe-rich droplets. The higher the body force is produced, the larger the distance will be covered due to the migration of the droplets. Further analysis reveals that the convection attributed to the thermoelectric effect may contribute to the migration of the Fe-rich droplets at a low magnetic field and become negligible at high magnetic flux densities.